Social Skill Strategies Used by Teachers in Mainstream Secondary Schools with Students Living on the Autism Spectrum - Harris-Howson, Cerys Ann (Curtin University, 2025)
The prevalence of adolescent students living on the autism spectrum is continuing to increase in Australia, demonstrating the importance of educators developing students’ social skills. This research indicated teachers in mainstream secondary schools prioritise developing conflict resolution skills. Teachers commonly implemented discussions, perceiving them to be effective. However, they suggested effectiveness could be improved with increased consistency. While teachers deemed the strategies effective, this was not without challenge, particularly during the COVID-19 pandemic.